2009
DOI: 10.1002/cne.22241
|View full text |Cite
|
Sign up to set email alerts
|

Regional and subcellular distribution of HDAC4 in mouse brain

Abstract: Histone deacetylases (HDACs) are part of a system that links epigenetic control of gene expression to a variety of environmental stimuli. Some HDACs, including HDAC4, shuttle between the cytoplasm and nucleus in response to physiological cues such as calcium signaling. HDAC4 mRNA is enriched in the brain, but the regional and subcellular protein expression pattern of HDAC4 is not known. Here we show that HDAC4 is more highly expressed in some brain regions than in others. HDAC4 is present in the perikaryial cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
86
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(97 citation statements)
references
References 64 publications
(81 reference statements)
9
86
0
2
Order By: Relevance
“…In neuronal cells, HDAC4 is primarily localized in the cytoplasm (10,17,18) but it can accumulate in the nucleus in conditions of deprived synaptic activity (10,18) and in neuronal pathologies (20)(21)(22)(23)(24). In particular, extrasynaptic N-methyl-D-aspartate receptors (eNMDARs) that trigger excitotoxicity (25) have been associated with many neurodegenerative diseases (25)(26)(27)(28).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In neuronal cells, HDAC4 is primarily localized in the cytoplasm (10,17,18) but it can accumulate in the nucleus in conditions of deprived synaptic activity (10,18) and in neuronal pathologies (20)(21)(22)(23)(24). In particular, extrasynaptic N-methyl-D-aspartate receptors (eNMDARs) that trigger excitotoxicity (25) have been associated with many neurodegenerative diseases (25)(26)(27)(28).…”
Section: Resultsmentioning
confidence: 99%
“…In neurons, at resting conditions, HDAC4 is predominantly localized in the cytoplasm (17), where it appears to promote neuroprotective gene expression (32,33). Indeed, synaptic activity-induced nuclear calcium-signaling, known for its survival-enhancing effects (34)(35)(36)(37), has been shown to promote HDAC4 nuclear export (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While HDAC4 is expressed in the brain (33) and has a known role in synaptic plasticity (12,34), much less is known about the function of ESRRA in the brain. Several lines of evidence, however, support our finding that decreases in ESRRA activity may be relevant to neuronal dysfunction in ED patients.…”
Section: Discussionmentioning
confidence: 99%
“…RNA interference-induced reduction of Ubc9 in the adult brain impaired long-term memory in the courtship suppression assay, a Drosophila model of associative memory. We also demonstrate that HDAC4 and Ubc9 interact genetically during memory formation, opening new avenues for investigating the mechanisms through which HDAC4 regulates memory formation and other neurological processes.KEYWORDS histone deacetylase; SUMOylation; plasticity; neuron; memory T HE histone deacetylase HDAC4 is widely expressed in neurons throughout the brain (Darcy et al 2010) and an increasing body of evidence indicates that HDAC4 plays important roles in neurological function Chen and Cepko 2009;Kim et al 2012;Li et al 2012;Sando et al 2012;Sarkar et al 2014). To that end, we recently demonstrated that in Drosophila, RNA interference (RNAi)-mediated knockdown of HDAC4 in the adult brain impairs long-term memory (LTM) in the courtship suppression assay, a model of associative memory (Fitzsimons et al 2013).…”
mentioning
confidence: 99%